Analisis Tingkat Perkembangan Wilayah dan Pola Spasial Sub Sektor Pertanian Hortikultura di Pulau Timor Provinsi Nusa Tenggara Timur - Anggelina Delviana Klau; Werenfridus Taena; Marce Sherly Kase; Frieds Allung Amu Blegur; Felisisima Afoan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
The development of a region has a high relationship with the concentration of economic activity that occurs in an area, so the region's development can be seen based on the centre of its activities. The purpose of this study was to identify the level of regional development in the regencies on the island of Timor, NTT and the typology and spatial pattern of the linkages of the horticulture sub-sector, which are commodities of interaction between regions on the island of Timor, NTT. The analytical method used in this research is scalogram analysis for regional development level and Moran index analysis for typology and spatial pattern of horticultural commodities. Based on the results of the analysis to find out the level of regional development in the regencies on Timor Island, NTT, it can be seen that Kupang Regency has the most complete availability of facilities and infrastructure so that it becomes hierarchy I, namely serving regencies on Timor Island, NTT, Hierarchy II is Belu Regency and then TTU Regency. The last one is TTS Regency and Malacca Regency occupying hierarchy III. Furthermore, Moran index analysis was used to determine the typology and spatial pattern of the horticulture sub-sector. The analysis results showed that the distribution pattern was clustered for the shallots. The distribution pattern was spread for the squash and carrot commodities, while for the tomatoes and bananas, the distribution pattern was clustered, with each LIS cluster category having low-high and high-low categories.